Oral Toxicological Studies of Pueraria Flower Extract: Acute Toxicity Study in Mice and Subchronic Toxicity Study in Rats. Issue 11 (November 2013) - Takano, Akira; Kamiya, Tomoyasu; Tsubata, Masahito; Ikeguchi, Motoya; Takagaki, Kinya; Kinjo, Junei
Abstract Kudzu has been widely used as an herbal medicine in China. The root of the kudzu is also well known as an antipyretic and analgesic in treatment of the common cold, while its flower has been used to treat alcohol intoxication, alcohol abuse, and dysentery. Pueraria flower extract (PFE) is a hot water extract derived from the flower of the kudzu, Pueraria thomsonii Benth. (Fabaceae), oral intake of which exhibits anti‐obesity properties in mice and humans. In this study, we conducted acute and subchronic toxicity studies for an evaluation of safety. In the acute study, PFE (5 g/kg body weight) was orally administered to ddY mice. For 14 d after administration, no deaths or abnormal changes were observed in general signs, body weight (BW), or food consumption, and no abnormal findings were observed in the major organs and tissues of either males or females at necropsy. The oral LD50 of PFE was therefore estimated to be higher than 5 g/kg BW. In the subchronic study, PFE was mixed into the diet in place of powdered CRF‐1 and administered at concentrations of 0% (control), 0.5%, 1.5%, and 5.0% to male and female Sprague–Dawley rats for 90 d. No mortality or toxicological changes were observed during the experimental period. Blood biochemical, hematological, and urinary parameters revealed no toxicologically significant changes. Furthermore, no anatomical or histopathological changes due to PFE were observed. The no‐observed adverse‐effect‐level of PFE was thus estimated to be 5.0% in the diet (male: 3.0 g/kg BW/d; female: 3.5 g/kg BW/d).